Four cases of HLA-A*26(+)/B*51(−) intestinal Behçet's disease without abdominal symptoms. (2nd January 2019) - Kobashigawa, Tsuyoshi; Nanke, Yuki; Yamanaka, Hisashi; Kotake, Shigeru
Abstract: Behçet's disease (BD) is a systemic inflammatory disorder and involvement of the bowel leads to a poor prognosis due to perforation of intestinal ulcers and penetration of ulceration into surrounding organs. We describe the clinical features of 4 Japanese BD patients (1 male) with intestinal lesions detected by colonoscopy, and the 4 patients had no abdominal complaints at their first admission to our hospital from 2003 to 2005. Case 1 was a 74-year-old woman, Case 2 was a 25-year-old woman, Case 3 was a 32-year-old woman, and Case 4 was a 32-year-old man. The characteristics of BD which they all had in common were recurrent oral aphthous ulcers, erythema nodosum, acneiform eruption, genital ulcers, polyarthritis and gastrointestinal lesions without abdominal complaints. None of these patients were positive for HLA-B*51, but all of them had HLA-A*26. Our findings suggest that screening colonoscopy is important for diagnosing intestinal BD in order to achieve a good prognosis.